Electrically powered repeatable air explosions using microtubular graphene assemblies. (September 2021) - Schütt, Fabian; Rasch, Florian; Deka, Nipon; Reimers, Armin; Saure, Lena M.; Kaps, Sören; Rank, Jannik; Carstensen, Jürgen; Kumar Mishra, Yogendra; Misseroni, Diego; Romani Vázquez, Adrian; Lohe, Martin R.; et al.
Graphical abstract: Abstract: Controllable rapid expansion and activation of gases is important for a variety of applications, including combustion engines, thrusters, actuators, catalysis, and sensors. Typically, the activation of macroscopic gas volumes is based on ultra-fast chemical reactions, which require fuel and are irreversible. An "electrically powered explosion", i.e., the rapid increase in temperature of a macroscopic relevant gas volume induced by an electrical power pulse, is a feasible repeatable and clean alternative, providing adaptable non-chemical power on demand. Till now, the fundamental problem was to find an efficient transducer material that converts electrical energy into an immediate temperature increase of a sufficient gas volume. To overcome these limitations, we developed electrically powered repeatable air explosions (EPRAE) based on free-standing graphene layers of nanoscale thickness in the form of microtubes that are interconnected to a macroscopic framework. These low-density and highly permeable graphene foams are characterized by heat capacities comparable to air. The EPRAE process facilitates cyclic heating of cm 3 -sized air volumes to several 100 °C for more than 100, 000 cycles, heating rates beyond 300, 000 K s −1 and repetition rates of several Hz. It enables pneumatic actuators with the highest observed output power densities (>40 kW kg −1 ) and strains ∼100%, as well as tunable microfluidic pumps, gas flowmeters, thermophones, and micro-thrusters.